Development of a Stakeholder Satisfaction System Model for Service and Education Quality - Wahyuni, Sri; Zamroni; Apriani, Rizka; Fajarianto, Otto; Yuniawatika; Syarifa, Najwa Kamila; Kusumaningtyas, Fitri Indra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study aims to measure the level of stakeholder satisfaction with the quality of service and education at the Faculty of Education, State University of Malang. The research employs a quantitative analysis method, utilizing a structured questionnaire based on five service quality indicators: Tangible, Responsiveness, Reliability, Empathy, and Assurance. The questionnaire was distributed to stakeholders, including students, lecturers, and staff. The results indicate that the overall level of stakeholder satisfaction is high, with the Assurance indicator scoring the highest at 76.6%, reflecting strong trust in services provided. The lowest score was observed in the Responsiveness indicator at 72.8%, suggesting a need for improvement in addressing stakeholder needs promptly. The study is limited to stakeholders at the Faculty of Education, and the findings may not be generalizable to other faculties or institutions. The findings provide valuable insights for the Faculty of Education to enhance service quality, particularly in responsiveness, to better meet stakeholder expectations. This research contributes to the ongoing efforts to improve educational service quality by providing empirical data on stakeholder satisfaction within a specific academic context.